Perspective Differences Between Universities and Industries in Developing Engineering Students with Non-Technical Skills - Azmi, Aini Najwa; Kamin, Yusri; Md Nasir, Ahmad Nabil; Noordin, Muhammad Khair (Journal of Technical Education and Training, 2020)
Non-technical skill is the main attribute for a fresh engineering graduate to be employed. Recently, there are many complaints from industries regarding their non-technical skills. Many studies revealed that these skills could be developed effectively through industrial training. This paper is presenting the differences in the perspectives between universities and industries in non-technical skills development among engineering students. A qualitative study has been done on the experts which were five industrial training coordinators from universities and five employers from the industry. The experts were chosen based on are selected based on specific qualities to obtain the most relevant data. The transcribed interview data were analysed by using thematic analysis. The result reveals that there are some of miscommunication between universities and industries. It seems that universities are not able to fulfil what industry wants because of some unavoidable conditions. As mentioned before that industrial training is a very good time for student to develop their nontechnical skills. Five components are discussed namely placement in the industry, training duration, assessment, type of training or task given and learning outcomes. There are some similarities and differences between universities and industries regarding factors that are affecting non-technical skills development during industrial training. Universities should minimize the gap to ensure the students can get the most valuable experience during their industrial trainings as that can be the best platform for students to learn and enhance their non-technical skills.